Minat Peserta Didik Dalam Mengikuti Pelajaran di Sekolah Menengah Pertama - Hendri Hendri (Anterior Jurnal, 2013)
This study aimed to figure out and describe learners’ interest in the learning process. This study was done in SMP Negeri 1 Binjai academic year 2010/2011. The method approach was quantitative, where all information and data realized in quantitative or numbers, the analysis based on the statistic analysis. The population was 536 learners. The technique of sample collection with proportional random sampling by taking 15% of the population numbers or 80 learners. The method of data collection to identify the variable used questioner. Based on the answer discretion it is the close questioner. The result showed that (1) learners’ interest in the learning process caused by a sense of excitement, attention, and positive attitude to the lesson. (2) based on the level of interest in learning process the higher and the lower category as follow: (a) positive attitude to lesson 35,00% in high category, (b) learners’’ attention to lesson 27,92% in high category, and (c) sense of excitement to lesson 26,07% in high category, and (3) it can be concluded that learners’ interest in the learning process in SMP Negeri 1 Binjai academic year 2012/2011 in high category with percentage 29,66%.